The experience of adoptive parents in adoption reunion relationships: A qualitative study. - Petta, G.; Steed, Lyndall (American Orthopsychiatric Association, Inc, 2005)
The issues experienced by adoptive parents when faced with an adult child's searching or reunion relationship with birth families, how adoptive parents place themselves within this process, and factors that influence their experience at this time are explored in a qualitative study of 21 adoptive parents. Themes derived from semi-structured interviews are discussed, and implications for clinical practice and future research are suggested.